Social media, a handtool for News gathering?: a case study of the Newsday and Southern Eye - Kaonza, Cristabel Varaidzo (Midlands State University, 2017)
The main aim of the research is to examine the dynamics of using social media as a source for news in mainstream media. The research will also seek to highlight the potential threat to journalists’ ethics such as objectivity, bias and fairness as a result of sourcing out information from various social media platforms such as Facebook pages, Twitter, Instagram and Whatsapp. The use of social media as a source for news by mainstream media newspapers especially those operating from the private media is as a result of the polarised nature that the media operates in, and at times forced these journalists to source out information from social media. The use of social media platforms has seen journalists accessing information at ease, and these various platforms have been viewed as a democratic tool that has changed story narratives. Newsday and Southern Eye have enjoyed the use of social media, although at a limited rate as they can easily access information from public bodies.